2013
DOI: 10.1038/embor.2013.167
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with both ZNRF3 and LGR4 is required for the signalling activity of R‐spondin

Abstract: R-spondin proteins sensitize cells to Wnt signalling and act as potent stem cell growth factors. Various membrane proteins have been proposed as potential receptors of R-spondin, including LGR4/5, membrane E3 ubiquitin ligases ZNRF3/RNF43 and several others proteins. Here, we show that R-spondin interacts with ZNRF3/RNF43 and LGR4 through distinct motifs. Both LGR4 and ZNRF3 binding motifs are required for R-spondin-induced LGR4/ZNRF3 interaction, membrane clearance of ZNRF3 and activation of Wnt signalling. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 25 publications
4
76
0
1
Order By: Relevance
“…A simultaneous study systematically mutating all conserved Furin repeat residues independently found that the R66A and Q71A mutations in the Furin1 domain completely abolish R-spondin-ZNRF3 binding. All studies agree that R-spondin-4 residues that are mutated in anonychia patients reside in the center of this interface Peng et al 2013b;Xie et al 2013;Zebisch et al 2013). These observations explain the inactivity of diseaserelated R-spondins in Wnt reporter assays despite intact Lgr5 binding (Peng et al 2013a;Xie et al 2013;Zebisch et al 2013).…”
Section: R-spondin Rnf43/znrf3supporting
confidence: 51%
See 1 more Smart Citation
“…A simultaneous study systematically mutating all conserved Furin repeat residues independently found that the R66A and Q71A mutations in the Furin1 domain completely abolish R-spondin-ZNRF3 binding. All studies agree that R-spondin-4 residues that are mutated in anonychia patients reside in the center of this interface Peng et al 2013b;Xie et al 2013;Zebisch et al 2013). These observations explain the inactivity of diseaserelated R-spondins in Wnt reporter assays despite intact Lgr5 binding (Peng et al 2013a;Xie et al 2013;Zebisch et al 2013).…”
Section: R-spondin Rnf43/znrf3supporting
confidence: 51%
“…Single F106E or F110E mutations in the F clamp completely abrogate receptorligand binding as well as the functional activity of R-spondin, as tested in Wnt reporter assays and small intestinal stem cell cultures (Peng et al 2013a). Similarly, F106A and F110A mutations disrupt interaction with Lgr4 (Wang et al 2013a;Xie et al 2013). A second Lgr5 interaction site in R-spondin has a charged character and centers around Lys59 (Furin-1) and Arg87 (Furin-1).…”
Section: Lgr/r-spondinmentioning
confidence: 99%
“…8B). The structures and mutagenesis data (Peng et al, 2013b;Xie et al, 2013;Zebisch et al, 2013) indicated that two conserved RSPO residues are most critical for ZNRF3/RNF43 binding: R66 and Q71 (RSPO1 numbering), which are located on the b-strands of the second b-hairpin of Fu1 and face into a shallow cleft on the ZNRF3/RNF43 surface (Figs. 4B and 8A).…”
Section: Resultsmentioning
confidence: 99%
“…LGR4/5/6 have a large extracellular domain (ECD) with 17 leucine-rich repeats (LRR) that provide the RSPO binding site, and ZNRF3/RNF43 have a small ECD for RSPO binding. Crystal structures of binary and ternary complexes Peng et al, 2013a,b;Wang et al, 2013;Xu et al, 2013;Zebisch et al, 2013) and mutagenesis studies (Xie et al, 2013) indicated that distinct regions of RSPO Fu1-Fu2 contact the two receptors.…”
Section: Introductionmentioning
confidence: 99%
“…RSPOs normally inhibit the activity of RNF43 and ZNRF3 by sequestering them into a heterotrimeric complex with LGR4/5/6 (Leucine-rich repeat containing G-protein-coupled receptors 4, 5, or 6). This complex results in the inhibition and membrane clearance of these E3 ubiquitin ligases, leading to increased Frizzled and LRP5/6 proteins on the cell surface (43,54). The LGR RSPO complex may also enhances b-catenin-dependent signaling by promoting MEK1/2-mediated phosphorylation of LRP5/6 and b-catenin-independent signaling through regulation of actin dynamics (55).…”
Section: R-spondin Translocations and Gene Amplificationmentioning
confidence: 99%